2022
DOI: 10.1186/s12870-022-03736-0
|View full text |Cite
|
Sign up to set email alerts
|

Plastome structure of 8 Calanthe s.l. species (Orchidaceae): comparative genomics, phylogenetic analysis

Abstract: Background Calanthe (Epidendroideae, Orchidaceae) is a pantropical genus distributed in Asia and Africa. Its species are of great importance in terms of economic, ornamental and medicinal values. However, due to limited and confusing delimitation characters, the taxonomy of the Calanthe alliance (Calanthe, Cephalantheropsis, and Phaius) has not been sufficiently resolved. Additionally, the limited genomic information has shown incongruences in its systematics and phylogeny. In this study, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 125 publications
4
5
0
1
Order By: Relevance
“…It suggests that the four most frequently used codons are AAA-K (1114), AUU-I (1093), GAA-E (1058) and UUU-F (982), accounting for 4.14%, 4.07%, 3.94% and 3.65% among all codons, respectively ( Table S2 and Figure 3 ). Similar to the previous results for other angiosperms, most of the codons ending with A or T have RSCU values greater than 1, while, most of those ending with C or G have RSCU values of less than 1 [ 25 , 26 , 27 ].…”
Section: Resultssupporting
confidence: 87%
“…It suggests that the four most frequently used codons are AAA-K (1114), AUU-I (1093), GAA-E (1058) and UUU-F (982), accounting for 4.14%, 4.07%, 3.94% and 3.65% among all codons, respectively ( Table S2 and Figure 3 ). Similar to the previous results for other angiosperms, most of the codons ending with A or T have RSCU values greater than 1, while, most of those ending with C or G have RSCU values of less than 1 [ 25 , 26 , 27 ].…”
Section: Resultssupporting
confidence: 87%
“…Compared to other Collabieae species, the S. aurea cp genome shows a highly conserved structure without any gene loss. The quadripartite structure and gene compositions are consistent with previously reported Collabieae species (9,10,40). In Figure 5, gene inversion was observed in the Collabium formosanum cp genome because of its different orientation submitted in the GenBank (41).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, S. aurea shows a further relationship with other species (Clade A); in particular, Cephalantheropsis and Phaius also reside in the same clade as Calanthe . Despite several differences in morphological characteristics, a number of molecular studies (9,44) including the present study have consistently shown that these two genera are positioned within the Calanthe clade. For the Phaius species, the morphological characteristic differences are minimal compared to those of the Calanthe species.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…et Styloglossum Breda au niveau générique. Récemment, l'analyse du plastome de huit espèces de l'alliance Calanthe confirme la polyphylie (Chen et al 2020; Nanjala et al 2022).…”
Section: Introductionunclassified